Harvest and crippling rates of mourning doves in Missouri - John H. Schulz; Thomas W. Bonnot; Joshua J. Millspaugh; Tony W. Mong (Wildlife Society Bulletin)
Abstract Mourning dove (Zenaida macroura) harvest management requires an assessment of birds shot and not recovered (hereafter, “crippled doves”) to fully determine harvest mortality. However, estimating crippling rates is challenging. We estimated mourning dove harvest mortality, which included crippling rates, on a public hunting area in Missouri, USA, by monitoring radiomarked doves. We also compared crippling rates of radiomarked doves with hunter‐reported estimates of crippling. During 2005–2008, we estimated annual harvest mortality between 23% and 30% on the area. Crippling rates ranged from 18% to 50% of harvest mortality in radiomarked doves. In comparison, hunter‐reported crippling rates during 2005–2011 (14–18%) were, on average, 30% lower but more consistent than estimates from radiomarked doves. During 2005–2008, harvest mortality of radiomarked doves was 27%, with one‐quarter of this mortality coming from crippled doves. Our empirical results confirm previous reports that crippling is a sizeable component of dove harvest. The potential bias in hunter‐reported crippling rates could result in overharvest if not considered. Therefore, future harvest management decisions should not overlook the potential impacts of crippling on populations, especially on locally managed public hunting areas. © 2013 The Wildlife Society.